The Influence of Rate, Service Quality, Core Service Benefit, and Place Utility on Patient Satisfaction - Ni Ketut Rupini; Nuraeni, Neni; Sarfilianty Anggiani (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The healthcare service industry continuously strives to enhance patient satisfaction, a key indicator for evaluating service quality and competitiveness. These imperative challenges hospitals to provide services that not only meet quality standards but are also economically accessible to the broader community. Drawing upon the expectancy-disconfirmation theory (EDT) and ServQual model, this study aims to analyze how patient expectations and perceptions regarding tariff, service quality, core service benefits, and location utility influence their overall satisfaction. Using a quantitative approach, data were collected from a sample of 110 inpatients receiving general care at Dr. Sitanala National Public Hospital (RSUP Dr. Sitanala) in Tangerang. Structured questionnaires were distributed via Google Forms to purposively sampled patients who met specific criteria. Data analysis was conducted using SmartPLS 3.0 software. The findings reveal that tariffs have a negative and non-significant effect on patient satisfaction, suggesting that while cost is a consideration, it may not significantly disconfirm expectations or is outweighed by other factors. Conversely, service quality, core service benefits, and location utility each have a positive and significant impact on patient satisfaction, aligning with EDT's premise that perceived performance meeting or exceeding expectations in these areas leads to higher satisfaction. This study offers important insights for future research, particularly by examining these variables collectively within an EDT framework and highlights the diverse dimensions influencing patient satisfaction in healthcare.